STUDY OF FERTILIZER COSTS USING FERTILIZER SPREADER ON OIL PALM PRODUCING CROPS IN PULAU TIGA PLANTATION PT. PERKEBUNAN NUSANTARA IV REGIONAL VI KSO - Fahmi, Dimas Maulana; Sinaga, Nurkhotimah; Ningsih, Tuty; Manurung, Hamzah (International Journal of Economic, Technology and Social Sciences (Injects), 2025)
The highest cost proportion in the maintenance costs of oil palm plantations is the cost of fertilization. One of the mechanical fertilization methods uses a Fertilizer Spreader. The purpose of this study was to examine the cost of fertilization using a Fertilizer Spreader on Mature Plants (TM) of oil palm in Afdelling II and III of Pulau Tiga Plantation of PT. Perkebunan Nusantara IV Regional VI KSO in 2024. The research method used a quantitative descriptive method. The research data were analyzed using Parametric Test Analysis, namely the Independent Sample T-Test with a level of ? = 5%. The parameters observed were the components of the fertilization costs of oil palm Mature Plants (TM) at PT. Perkebunan Nusantara IV Regional VI KSO, as well as the differences in the costs of fertilizing oil palm mature plants in Afdelling II and Afdelling III at PT. Perkebunan Nusantara IV Regional VI KSO. The results of the study showed that the composition of the costs of mechanical fertilization using a Fertilizer Spreader on oil palm plantations consisted of fertilizer purchase costs, transportation costs, loading costs to trucks, loading and unloading costs to the Spreader, fuel costs and operator costs. The largest composition of mechanical fertilization costs in the last 3 years in oil palm Producing Plants (TM) in Afdelling II is in the purchase of fertilizer with a percentage of 96.68%, or Rp. 4,623,833,780 while in Afdelling II the largest composition is the cost of purchasing fertilizer with a percentage of 96.93% or Rp. 3,401,494,919. The results of the independent sample T-test analysis test show a P-Value or Sig. (2-tailed) of 0.255> 0.05, so based on the basis of decision making that, there is no significant (real) difference between the fertilization costs of Afdelling II and Afdelling III in the Pulau Tiga Plantation of PT. Perkebunan Nusantara IV Regional VI KSO